Assessment of the effective CO2 storage capacity in the Beibuwan Basin, offshore of southwestern P. R. China. (June 2015) - Li, Pengchun; Zhou, Di; Zhang, Cuimei; Chen, Guanghao
Highlights: Beibuwan Basin may provide CO2 storage sites for several provinces in South China. The effective storage capacity of the basin is ∼48Gt CO2, and mainly in saline aquifers. The Weixinan Sag is the most promising area for CO2 storage in the basin. An offshore storage network centrolized on island might help reducing the cost. Abstract: The Beibuwan Basin is a petroliferous sedimentary basin in Beibu Gulf in the northwestern South China Sea. This basin is surrounded by Guangxi, Hainan and Guangdong Provinces. Previous studies show that the onshore CO2 storage potential in Southeastern China is limited; thus the CO2 storage potential of offshore basins, including Beibuwan Basin, is crucial for CO2 capture and storage implementation in these areas. This study evaluates the potential for CO2 geological storage in the Beibuwan Basin through a desktop evaluation of existing data, to provide background data for planning regional carbon emission reductions. Deep saline aquifers and hydrocarbon reservoirs within the basin were evaluated for their suitability to store CO2 based on geological, geographical and environmental criteria, and the effective storage capacity was estimated. The estimates show that the Beibuwan Basin has suitable geological conditions with three super reservoirs of high porosity (20–30%) and permeability (200–300 mD) and accompanying three widely distributed efficient sealing layers. The effective capacity for CO2 storage is 485.6 × 10 8  t CO2 in deep saline aquifers of Beibuwan Basin; this capacity could potentially support CO2 sequestration for large power plants onshore in the Beibu Gulf area. The storage capacity of the oil and gas fields is limited, with average values of 42.3 × 10 6  t CO2 and 62.3 × 10 6  t CO2, respectively. The most prospective area for CO2 storage in Beibuwan Basin is within the Weixinan Sag which contains the Weixinan oilfield groups and plenty of potential structural traps, depending on the availability of porous units, including those that are non-oil bearing. The effective CO2 storage capacity of the Weixinan Sag is 47.2 × 10 8  t CO2 . Existing geological and geophysical data and facilities, including wells, pipelines and platforms for hydrocarbon production might help reduce costs for offshore CO2 transportation and storage operations. The mode of the oil and gas terminal treatment plant on Weizhou Island provides a centralised management model for CO2 storage. If this mode can be utilised, an offshore CO2 transport and storage cluster can also be created in the Weixinan Sag greatly reducing the cost of offshore storage. Evaluation of the feasibility of using these oil production facilities for CO2 storage and of the risk along abandoned wells and faults is urgent.